Use of helminth therapy for management of ulcerative colitis and Crohn's disease: a systematic review. Issue 2 (28th February 2022) - Shields, Victoria Emma; Cooper, Jan
Abstract: Abstract: The incidence rate of inflammatory bowel diseases is increasing in developed countries. As such there is an increasing demand for new therapies. The aim of this systematic review was to investigate whether there is evidence to support the use of helminth therapy for the management of Crohn's disease and ulcerative colitis. Four databases (PubMed, Embase, Medline and the Cochrane Central Register of Control Trials) were searched for primary evidence in the form of clinical studies. Nine studies were suitable for inclusion: five double-blind randomized control trials and four open-label studies. This review divided the results of the studies into two categories: (a) the efficacy of helminth therapy and (b) the safety of helminth therapy. Results regarding the efficacy were mixed and a conclusive answer could not be reached, as there was not enough evidence to rule out a placebo effect. More research is needed, particularly studies with control groups to address the possibility of a placebo effect. Despite this, all nine studies concluded helminth therapy was safe and tolerable, and therefore there is currently no evidence against further exploration of this treatment option.